Bioboosters in the treatment of rheumatic diseases: a comprehensive review of currently available biologics in patients with rheumatoid arthritis, ankylosing spondylitis and psoriatic arthritis - Fabrizio Cantini (Dove Medical Press, 2009)
Fabrizio Cantini, Carlotta Nannini, Laura NiccoliSecond Division of Medicine, Rheumatology Unit, Hospital of Prato, ItalyAbstract: Immunologic research has clarified many aspects of the pathogenesis of inflammatory rheumatic disorders. Biologic drugs acting on different steps of the immune response, including cytokines, B- and T-cell lymphocytes, have been marketed over the past 10 years for the treatment of rheumatoid arthritis (RA), ankylosing spondylitis (AS), and psoriatic arthritis (PsA). Randomized controlled trials (RCTs) of anti-cytokine agents in RA (including the anti-tumor necrosis factor alpha (TNFα) drugs infliximab, etanercept, adalimumab, golimumab, certolizumab, anti-interleukin (IL)-1 anakinra, and anti-IL-6 tocilizumab) demonstrated a significant efficacy compared to traditional therapies, if combined with methotrexate (MTX), as measured by ACR 20, 50 and 70 response criteria. The new therapies have also been demonstrated to be superior to MTX in slowing or halting articular damage. RCTs have shown the efficacy of anti-TNFα in AS patients through significant improvement of symptoms and function. Trials of anti-TNFα in PsA patients showed marked improvement of articular symptoms for psoriasis and radiological disease progression. More recent studies have demonstrated the efficacy of B-cell depletion with rituximab, and T-cell inactivation with abatacept. All these drugs have a satisfactory safety profile. This paper reviews the different aspects of efficacy and tolerability of biologics in the therapy of RA, AS, and PsA.Keywords: anti-TNF, anti-cytokine agents, rituximab, abatacept, rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis